STUDI LITERATUR SISTEMATIS: FAKTOR PENENTU KEBERHASILAN PENERAPAN ERP DALAM ORGANISASI - Putri Ramadhani; Nur’Illiyyien Nur’Illiyyien; Aini Indrijawati; Muhammad Irdam Ferdiansyah (Universitas Islam Negeri Alauddin Makassar, 2023)
Enterprise Resource Planning (ERP) is considered by many organizations as a potential solution, essential for businesses to gain efficiencies and become competitive. ERP implementation can reap enormous benefits or it can be disastrous for an organization that fails to manage the implementation process. Adoption of a new ERP system is a very complex process and it is not as easy as one might think. The purpose of this research is to help practitioners and business people to increase the chances of success in implementing ERP in business. The results found from this literature study are factors that need to be considered during implementation, in order to facilitate the continued success of the ERP system and ensure a better impact. In the literature, we identified more than 30 CSFs, 12 of which were selected. Then, through recording the frequency of occurrence of the 12 factors identified in the literature, it is possible to provide a classification, which will help further investigations and ERP implementers to identify possible problems and to detect possible negative influences on project success